EFEKTIVITAS MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MENULIS PUISI - Siti Sopiyatul Marwah; Dian Hartati; Sahlan Mujtaba (Universitas Negeri Makassar, 2025)
This study aims to determine the effectiveness of the Project Based Learning model on the poetry writing learning outcomes of eighth-grade students at Al-Muslih Junior High School in Karawang. In this study, the Project Based Learning model was applied to poetry writing lessons in the eighth grade at Al-Mushlih Junior High School in Karawang. The method used in this study was quantitative with a quasi-experimental design. Data were obtained from pre- and post-tests. After the prerequisite tests were met, consisting of normality tests, homogeneity tests, and n-gain tests using SPSS version 25, the data were analysed using a t-test with a significance level of 5%. The results of the data analysis showed that there was an increase in the pre-test scores between the pre-test and post-test. This was evidenced by the average score improving from 54.0 to 76.8. The n-gain test results from this study indicate that the Project-Based Learning model is effective when applied to poetry writing instruction.